Do social exclusion and parental attitudes predict online gaming addiction in adolescents? - Muezzin, Ece Emre; Arslan, Fatma Nur; Karaaziz, Meryem (Journal of Dependence, 2024)
Objective: This study aims to examine whether social exclusion and parental attitudes predict online gaming addiction in adolescents. Method: The sample consisted of 393 individuals, of which 4.6% (n=18) were females and 95.4% (n=375) were males, which was determined by the purposive sampling method. Socio-demographic Information Form, Online Gaming Addiction Scale (OGAS), Ostracism Experience Scale for Adolescents (OES-A) and Parental Attitudes Scale (PAS) were used to obtain the personal information of the participants in this study. Results: The findings showed that there was a positive and statistically significant correlation between the disruption sub-dimension of the OGAS and the OES disregard, exclusion and overall total at a moderate level and the acceptance/affection and psychological autonomy sub-dimensions of the PAS. There was a moderate statistically significant positive relationship between the achievement sub-dimension of the OGAS and the OES neglect, exclusion and overall total and there was a negative and statistically significant relationship with the acceptance/affection and psychological autonomy sub-dimensions of the PAS. There was a moderate statistically significant negative relationship between the economic gain sub-dimension of the OGAS and the psychological autonomy sub-dimension of the PAS. It was found that social exclusion and the autonomic parental attitude scale were significant predictors of online gaming addiction in adolescents. Conclusion: Social exclusion and autonomous parenting attitudes are effective on online game addiction in adolescents.